Determination of Benzoyl Peroxide in Flour Brightener with Microfluidic Chip-Based Flow-Injection Chemiluminescence - Wang, Xiaozhang; Wang, Chaohui; Zhang, Qunming; Wang, Jing; Zheng, Tengfei (Asian Journal of Chemistry, 2012)
Benzoyl peroxide (BPO) in flour brightener was determined with chip-based chemiluminescence reaction. The microfluidic chip was fabricated with PDMS using MEMS techniques and the flow-injection chemiluminescence experiments were performed. The conditions of experiments including sample inject and flow-rate were selected and optimized according to their different influences on detect results. The standard curve of relative chemiluminescence intensity and benzoyl peroxide concentration was constructed from the reaction of benzoyl peroxide and luminol solutions with specific concentration, respectively. The experimental results indicate that a good linear relation is formed between the chemiluminescence intensity and benzoyl peroxide concentration within 10-6-10-8 g mL-1. The detection limit is about 2 × 10-9 g mL-1 in benzoyl peroxide solution. At last, flour brightener samples bought from market were tested with this microfluidic chip system. The result was consistent well with the content of brightener tag. Some important topics of integrated chip were discussed including inject pump, active mixer and microheater.